Paying with information - Ayça Kaya (Theoretical Economics, 2023)
The founder of a start-up (principal) who has a project with uncertain returns must retain and incentivize an agent using promise of future payments and information gathering. The agent's effort incrementally advances production and such advance is a prerequisite for gathering new information. The principal decides how much information to gather based on these incremental advancements. The principal faces cash constraints. The agent's outside option is large relative to his effort cost. Equilibrium features one of two outcomes: immediate learning, whereby the agent's compensation is low, learning is immediate and retention is possible only conditional on the project being of high quality; or gradual learning, whereby the agent's compensation is high, learning is gradual, the agent never quits and effort is inefficiently high.
Keywords: C72; D82; D83; D86; 330; agency costs; information control; Informational incentives